Inequality of Opportunity for Education : The Case of Turkey - Ferreira, Francisco H. G.; Gignoux, Jérémie (World Bank, Ankara, 2017)
This paper seeks to measure inequality of opportunity for education in turkey, taking into account both the quantity (attainment) and the quality of schooling (achievement). Using DHS data, large gaps in age-enrollment profiles are documented across genders, regions, and family backgrounds. The gender gap is particularly pronounced in the Easter provinces, in rural areas, and for poorer and larger households. PISA data show that morally irrelevant circumstances also affect achievement. The lower bound for the share of the variance in test scores that is accounted for by such circumstances in between a quarter and a third, depending on the subject and on the procedure adopted to correct for sample selection. Among those circumstances, family background variables such as parental education, father's occupation and the ownership of books, cultural possessions and electronics, seem to account for the largest inequality shares. Once the composition of families is controlled for, spatial location is considerably less important.